ChemInform Abstract: 1, 3‐Disubstituted Imidazolium Hydroxides: Dry Salts or Wet Carbenes?. Issue 12 (14th March 2013) - Yuen, Alexander K. L.; Masters, Anthony F.; Maschmeyer, Thomas
Abstract Review: 83 refs.